Setting up a collaborative European Human biological monitoring study on occupational exposure to Hexavalent Chromium - Santonen, Tiina (2020)
Background: The EU human biomonitoring initiative, HBM4EU, aims to co-ordinate and advance human biomonitoring across Europe and develop new approaches for biomonitoring. Hexavalent chromium (Cr(VI)) is an important occupational carcinogen, which compounds are currently authorized in Europe. In addition, a binding limit value for occupational exposure to Cr(VI) has been recently agreed in EU. These regulatory actions emphasize the need for EU-wide data on exposure and sensitive biomarkers to assess the exposure. Here we describe the design of the multinational, collaborative project to support management of occupational exposure to Cr(VI). Methods: The study involves eight European countries and aims to recruit 400 workers performing Cr(VI) surface treatment or stainless steel welding. In addition to urinary chromium (U-Cr), exhaled breath condensate (EBC) and blood samples are collected for the analysis of Cr(VI)/Cr. Exposure data will be complemented with data on effect markers. Personal air and wipe samples are collected in parallel to help interpretation of biomonitoring results. Standardized questionnaires are used to collect contextual data, and samplings are done following the standard operational procedures developed to support standardization. Results: This occupational Cr(VI) study is the first that will be performed concurrently in multiple European countries using harmonized protocols for data gathering, sampling and analysis. Combining national standardized surveys the power of the study and the strength of the findings is greatly enhanced. Samplings are currently on-going and include companies ranging from micro-sized companies to large international companies. Final results are expected by the end of 2020. The presentation covers the background data on the tasks covered and the available external exposure data. Conclusions: Using this unique set-up including multiple countries and harmonized protocols we expect to create more comprehensive data for EU decision making. The data allows also the assessment of the feasibility of different biomarkers in the biomonitoring of Cr(VI).